PENGARUH INVESTMENT OPPORTUNITY SET TERHADAP KEBIJAKAN DIVIDEN DENGAN FIRM SIZE SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN MANUFAKTUR TAHUN 2011-2013 DI BEI - Abrianita Vika Nur Maharsi; Siti Puryandani; Rudi Suryo Kristanto (Magister Manajemen STIE Bank BPD Jateng, 2017)
Dividend policy is a decision to define the part received by shareholders according to the funds they invest as well as the part that will be retained by the company. Dividend payout ratio has been discussed in the financial sector by several researchers since 1961 when Miller and Modigliani proposed the theory of “Signalling Hypothesis”. There are many variables that affect dividend policy including profitability, debt policy, liquidity, growth, investment opportunity set,etc. In this research, Investment Opportunity Set (IOS) is choosen according to the hardness of this observation, the main purpose of this research is to study the proxy of IOS exactly. This research aimed to empirically test the effect of set investment opportunity to the dividend policy. The tested variable in this study was investment opportunity set measured by market-to-book value of equity while the moderating variable was firm size. The sample was 16 companies listed on Indonesian Stock Exchange (I.S.E) 2011-2013 selected through purposive sampling technique. The analytical statistic was a simple linear regression to test the absolute difference value of moderation. The results showed that the investment opportunity set has significant effect on dividend policy because the value of significance IOS less than rate of significance (0,045<0,05), it means that firm size moderation can be used as moderator between investment opportunity set and dividend policy because the value of significance firm size less than rate of significance (0,041<0,05).